Endophytic bacterial diversity of Avicennia marina helps to confer resistance against salinity stress in Solanum lycopersicum - Amjad Ali (Journal of Plant Interactions, 2017)
The current study aimed to explore the endophytic bacterial diversity of Avicennia marina and the potential roles of these endophytes in counteracting saline conditions in tomato plants. Molecular analysis revealed strains from Paenibacillus, Bacillus, Microbacterium, Citrobacter, Lysinibacillus, Halomonas, Virgibacillus, Exiguobacterium, and Vibrio. However, Bacillus pumilus AM11 and Exiguobacterium sp. AM25 showed significantly higher growth in saline media. In response to salinity stress, tomato plants treated with AM11 and AM25 showed significantly higher (∼15–23%) biomass, photosynthetic rate and pigment accumulation compared to controls. Salinity-exposed plants had significantly reduced growth and increased (three-fold) lipid peroxidation, whilst glutathione, catalase, and peroxidase activities were significantly reduced. In contrast, AM11, AM25, and methionine improved these physiochemical attributes. The study concludes that the application of bacterial endophytes from plants growing in saline conditions can offer other plants similar stress-resistance potential. Such halophytic bacterial strains can be used to improve plant growth in saline conditions.